ANALYSIS OF DIFFICULTIES OF MATHEMATICS EDUCATION STUDENTS IN BLENDED LEARNING AFTER COVID-19 PANDEMIC - Narpila, Suci Dahlya; Ammamiarihta, Ammamiarihta; Nababan, Siti Aminah (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
Entering the new normal era in the UINSU Medan, the campus has established a blended learning system as a learning method. Although blended learning is good as an alternative to learning method in the new normal era, it still had limitations. If viewed from the perspective of students, they have difficulties when took blended learning. This difficulty will certainly affect the learning outcomes of the students themselves. This of course cannot be left alone, it is necessary to in depth analysis of student difficulties when took blended learning and then find the right solution to solve these difficulties. This research focuses to find out students’ difficulties when taking Calculus Vector Class through blended learning method after COVID-19 pandemic era. This is a descriptive qualitative study. The subjects of this study are students of Calculus Vector class in the fourth semester of the Department of Mathematics Education, UINSU Medan. This research uses interview method and questionnaires as data collection instruments. The results show that students' difficulties are divided into technical difficulties, student adaptation difficulties, and lecturer adaptation difficulties. Learning strategies must be developed to address these difficulties and to bolster students’ adaptation to blended learning class